2009
DOI: 10.1681/asn.2008101106
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phosphorus Acutely Impairs Endothelial Function

Abstract: Excessive dietary phosphorus may increase cardiovascular risk in healthy individuals as well as in patients with chronic kidney disease, but the mechanisms underlying this risk are not completely understood. To determine whether postprandial hyperphosphatemia may promote endothelial dysfunction, we investigated the acute effect of phosphorus loading on endothelial function in vitro and in vivo. Exposing bovine aortic endothelial cells to a phosphorus load increased production of reactive oxygen species, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
331
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 349 publications
(369 citation statements)
references
References 37 publications
(54 reference statements)
16
331
3
4
Order By: Relevance
“…Other studies, including our investigation, demonstrated that elevation of extracellular phosphate levels could induce endothelial dysfunction by an increase in oxidative stress and apoptosis, and a decrease in eNOS activity 48,49) . Inhibition of phosphate transport activity by phosphonoformic acid or siRNA can inhibit both calcification in vascular smooth muscle cells 44,50) and oxidative stress in endothelial cells 48,49) . Therefore, the phosphate transport activity of type III sodium-dependent phosphate transporters is important in the development of vascular complications leading to arteriosclerosis.…”
Section: Cardiovascular Disease and Transporterssupporting
confidence: 56%
“…Other studies, including our investigation, demonstrated that elevation of extracellular phosphate levels could induce endothelial dysfunction by an increase in oxidative stress and apoptosis, and a decrease in eNOS activity 48,49) . Inhibition of phosphate transport activity by phosphonoformic acid or siRNA can inhibit both calcification in vascular smooth muscle cells 44,50) and oxidative stress in endothelial cells 48,49) . Therefore, the phosphate transport activity of type III sodium-dependent phosphate transporters is important in the development of vascular complications leading to arteriosclerosis.…”
Section: Cardiovascular Disease and Transporterssupporting
confidence: 56%
“…Furthermore, these data go along with biologic knowledge that both FGF-23 and ADMA interfere with the NO system and that inhibition of NO is a powerful mechanism prompting renal function loss in experimental models. Dietary phosphate load may itself induce endothelial dysfunction in experimental clinical studies in healthy humans, 31 whereas no such direct evidence exists for FGF-23. In the present study adjustment for serum phosphate or for a better indicator of phosphate burden (such as fractional phosphate excretion) did not modify the ADMA-FGF-23 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo experiments showed that a high phosphorus load acutely increases endothelial dysfunction by impairing vasodilation, raising the risk for cardiovascular disease. 67 High levels of serum phosphorus in healthy young adults have been associated with coronary atherosclerosis 68 and with left ventricular hypertrophy, 69 and high levels of serum phosphorus in a cohort study were associated with a 40% greater risk of heart failure. 70 A meta-analysis showed that serum phosphorus, but not serum calcium or PTH, was independently associated with mortality and risk for cardiovascular disease in CKD patients.…”
Section: Phosphate Toxicity Associated With Ectopic Calcificationmentioning
confidence: 99%